Active Subfractions, Phytochemical Constituents, Dipeptidyl Peptidase-IV Inhibitory Activity and Antioxidant of Leaf Extract from Hibiscus surattensis L. - Yuliet; Sukandar, Elin Y.; Adnyana, I.K. (Natural Products Journal, The, 2020)
Objective: This research aimed to investigate the mechanism of action of leaf extract and active subfraction from English wild sour or Hibiscus surattensis L., evaluating antioxidant activity, and determining phytochemical constituents potential for treating various ailments such as diabetes and hepatitis. Background: Antioxidant potential of ethanolic extracts of leaf and active subfractions (ethyl acetate and water fraction) were evaluated using 2,2-diphenyl-1-picrylhydrazyl, Ferric Reducing Ability of Plasma and Cupric Reducing Antioxidant Capacity assays. Methods: Analysis of total flavonoid and phenolic contents were expressed as Quercetin Equivalent and Gallic Acid Equivalent through spectrophotometric technique. Liquid Chromatography-Mass Spectrophotometry/Mass Spectrophotometry was used to identify phytochemical constituents. Results: The results showed that the ethyl acetate fraction was potentially inhibitory against dipeptidyl peptidase IV (IC50 17.947 ± 4.842μg/mL) and had a high free radical scavenging capacity (IC50 value of 44.10 ± 0.243μg/mL; Ferric Reducing Ability of Plasma and Cupric Reducing Antioxidant Capacity values were found to be 639.70 ± 0.3mg ascorbic acid equivalent/g and 174.89 ± 0.58mg ascorbic acid equivalent/100 g respectively). Ethyl acetate fraction showed high flavonoid and phenolic content with 684.67 ± 0.83mg Quercetin Equivalent/g and 329.23 ± 0.82mg Gallic Acid Equivalent/g. Liquid Chromatography-Mass Spectrophotometry/ Mass Spectrophotometry analysis showed the presence of major compounds, including kaempferol, morin, quercetin, and trifolin. Conclusion: These results may explain the use of these leaves in folk medicine in the control of diabetes through a new mechanism and by preventing diabetic complications by means of their antioxidant properties.
Keywords: phytochemistry